Growth and Yield of Okra Using Bio-Stimulant of Golden Apple Snails Extracts and Fertilizer on Ultisol - Dora Fatma Nurshanti; Defrian Defrian; Novriani Novriani (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2021)
Cultivation of okra on ultisol soils having poor physical, chemical and biological soil properties can be improved by administering a bio-stimulant extract of golden snails and combined with NPK fertilizer. This research objective was to study a combination of bio-stimulant treatment of golden apple snail extract and NPK fertilizer dosage in increasing the growth and yield of okra on ultisol soil. This study used a factorial completely randomized design with two factors.  The first factor was Bio-stimulant golden apple snails extract consisting of 4 treatment, and the second factor was levels of NPK fertilizer consisting of 3 treatment. Fertilizers had a significant effect on increasing overall plant growth.  The bio-stimulant extracts of golden apple snails contain organic materials that can improve physical properties (increasing aggregation, moisture retention, soil hydraulic conductivity), chemical (increasing soil organic carbon content) and biology (increasing soil microbial biomass). The nutrient content in NPK fertilizers can increase nutrients; the availability of nutrients in the soil is balanced and can be absorbed by plants so that the photosynthesis process in plants can run well and increase on growth and yield of okra. The combination of bio-stimulant extract of golden apple snails of 20 mL/L water and NPK fertilizer of 150 kg/ha (1 g/polybag) had the highest resulted in the average value of growth and yield of okra on the ultisol soils.